Marriage and parenthood (London : Friends' Book Centre)
1934-11 1934 1930s 22 pages 1 THE ENGAGEMENT "Mind that which is pure in one another, which joins you together." George Fox. Marriage is the union of two personalities in a spiritual, intellectual, and physical adventure. It is a relationship not lightly to be entered into, for only those who accept its full implications and responsibilities can draw from it the rich experiences which it offers. The period of "falling in love", and being engaged, is one of the most wonderful periods in the life of the normal man and woman. It provides a necessary and valuable interlude between casual friendship and the ultimate intimacy of marriage, and gives the young couple an opportunity of learning to know and understand each other. During this time, when every pair of lovers from time immemorial has found the discussion of themselves and all that concerns them of absorbing interest, opportunity should be taken for frank and open consideration of the problems that are likely to confront them during the early part of their married life. Are the facts about the physical side of marriage known to both? Is parenthood to be by accident or design? Are children to be desired in the first year of marriage? Is the size of the family to be limited, and the advent of the children to be deliberately spaced, and, if so, by what means? Questions such as these will arise naturally between two young people who are giving serious thought to the planning of their future life together. Experience has shown that, far from robbing their married life of any of its richness and mystery, the lovers will, by this preliminary "clearing of the air", avoid many of the difficulties and pitfalls which await less prepared couples, and their union will be founded on a deep mutual respect and understanding. Doubtless many of the theories evolved during the engagement will be altered in the light of fuller experience, and both will realise that their ideas at this stage can only form a working hypothesis, but even this is infinitely better than undertaking a vast new enterprise without any plan of action at all. (5) 15X/2/478/6